2017
DOI: 10.1080/15504263.2017.1287455
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Interaction Between Smoking and Depressive Symptom Clusters With Coronary Artery Calcification: The CARDIA Study

Abstract: Objective Depressive symptom clusters are differentially associated with prognosis among patients with cardiovascular disease (CVD). Few studies have prospectively evaluated the association between somatic symptoms and risk for CVD. Previously, we observed that smoking and total depressive symptoms were synergistically associated with coronary artery calcification (CAC). The purpose of this study was to determine whether the smoking by depressive symptoms interaction, measured cumulatively over 25 years, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…A consideration for future studies is that certain clusters of depressive symptoms (e.g., somatic symptoms), rather than a global assessment, may have a greater influence on CVH compared to others, as has been frequently demonstrated among patients with CVD (Baune et al 2012). A 2017 analysis of CARDIA evaluating the interaction between depressive symptom clusters and smoking found that only somatic symptoms of depression significantly interacted with smoking exposure to predict greater odds of CAC (Carroll et al 2017a), while a 2012 analysis of CARDIA found that the negative affect cluster was associated with risk of developing CAC more so than somatic symptoms or other symptom clusters (Stewart et al 2012). Fewer studies have examined this association with incident CVD, but a 2014 study demonstrated that somatic symptoms of depression were associated with incident CAD events (Hawkins et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A consideration for future studies is that certain clusters of depressive symptoms (e.g., somatic symptoms), rather than a global assessment, may have a greater influence on CVH compared to others, as has been frequently demonstrated among patients with CVD (Baune et al 2012). A 2017 analysis of CARDIA evaluating the interaction between depressive symptom clusters and smoking found that only somatic symptoms of depression significantly interacted with smoking exposure to predict greater odds of CAC (Carroll et al 2017a), while a 2012 analysis of CARDIA found that the negative affect cluster was associated with risk of developing CAC more so than somatic symptoms or other symptom clusters (Stewart et al 2012). Fewer studies have examined this association with incident CVD, but a 2014 study demonstrated that somatic symptoms of depression were associated with incident CAD events (Hawkins et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Bu faktörlerin birleşmesi ile endotel fonksiyonları bozulmakta, böylece koroner arterlerde ateroskleroz gelişmektedir. [17,[27][28][29][30][31] Ayrıca literatüre bakıldığında tedavi gereksinimi olan KAH olgularında daha yüksek kan basıncı düzeylerinin saptandığı gözlenmiştir. [18,[29][30][31] Bu faktörlerin yanında depresif duygudurum ile tetiklenen nöroendokrin sistemin insulin direnci arışı ile metabolik sendrom riskini artırdığı, obezite, kanser, Tip 2 diabetes mellitus ve hipertansiyon gibi birçok hastalık için de risk faktörü olduğu görülmektedir.…”
Section: Discussionunclassified
“…[17,[27][28][29][30][31] Ayrıca literatüre bakıldığında tedavi gereksinimi olan KAH olgularında daha yüksek kan basıncı düzeylerinin saptandığı gözlenmiştir. [18,[29][30][31] Bu faktörlerin yanında depresif duygudurum ile tetiklenen nöroendokrin sistemin insulin direnci arışı ile metabolik sendrom riskini artırdığı, obezite, kanser, Tip 2 diabetes mellitus ve hipertansiyon gibi birçok hastalık için de risk faktörü olduğu görülmektedir. [23][24][25][26][27] Anksiyetenin kardiyovasküler bozuklukların gelişiminde rol oynadığı bilinmektedir.…”
Section: Discussionunclassified
“…Previous studies had examined the interaction between depression and other characteristics. For instance, it was well-established in some studies about the multiplying effect between smoking exposure and depressive symptoms on promoting atherosclerosis and heart disease 26,40 . Lou et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recall bias could have potentially affected our results because the interview was often based on parental recall after the birth of the child, especially when it came to assessing depression. Although controls were randomly matched at the rate of 1:2 by age of child, we may have missed some depressive symptom 40 . Moreover, colds and fever were largely determined by maternal self-reports, which it may lead to false exposure classification, and it was possible to miss a fever because women may be reluctant to disclose such information 47 .…”
Section: Discussionmentioning
confidence: 99%